Diagnostic cut‐off of Aspergillus fumigatus‐specific IgG in the diagnosis of chronic pulmonary aspergillosis - Sehgal, Inderpaul Singh; Choudhary, Hansraj; Dhooria, Sahajal; Aggarwal, Ashutosh Nath; Garg, Mandeep; Chakrabarti, Arunaloke; Agarwal, Ritesh (Mycoses, 2018)
Aspergillus fumigatus‐specific IgG is pivotal in making the diagnosis of chronic pulmonary aspergillosis (CPA). However, the cut‐off value for A. fumigatus‐specific IgG remains unknown. We included consecutive treatment‐naïve subjects with chronic cavitary pulmonary aspergillosis (CCPA, cases). The controls were subjects with treated pulmonary tuberculosis, who had residual radiological abnormality and minimal symptoms. The diagnosis of CCPA was based on consistent clinicoradiological features along with demonstration of Aspergillus infection (growth of Aspergillus in sputum or bronchoalveolar lavage fluid [BALF] culture; serum or BALF galactomannan index >0.5 and >1, respectively). For determining the cut‐off of A. fumigatus‐specific IgG (Phadia), subjects were randomly classified as derivation (two‐thirds) and validation (one‐third) cohort. One hundred and thirty‐seven cases and 50 controls were included. The best cut‐off value for A. fumigatus‐specific IgG (derivation cohort) was 27.3 mgA/L (AUROC, 0.976) at a sensitivity and specificity of 95.6% and 100%, respectively. Using a cut‐off of 27 mgA/L, the sensitivity and specificity in the validation cohort was 91.3% and 100%, respectively. In contrast, the sensitivity of Aspergillus precipitins was only 25.5%. At a cut‐off value of 27 mgA/L, A. fumigatus‐specific IgG is a reliable test with high sensitivity and specificity in the diagnosis of CPA. More studies are required to confirm our findings.